Control system design an introduction to state-space methods - Friedland, Bernard (Dover Publications, 2005)
Introduction to state-space methods covers feedback control; state-space representation of dynamic systems and dynamics of linear systems; frequency-domain analysis; controllability and observability; and shaping the dynamic response. Additional subjects encompass linear observers; compensator design by the separation principle; linear, quadratic optimum control; random processes; and Kalman filters. 1986 edition.
Originally published: New York : McGraw-Hill, c1986.
Keywords: Automatic control.; Control theory.; System design.; State-space methods.; elektronické knihy; electronic books